Methods of Asking and Answering Questions in Jadal Works Written by Fiqh Scholars - Abdurrahim Bilik (İslam Tetkikleri Dergisi)
After the death of the Prophet, Muslims began to investigate the legal rulings of Islam and apply them to the legal issues they faced. Consequently, different methods have emerged about how to approach the Qur’an and the Sunna, the main sources of Islam and Islamic tradition, and various views have emerged about the issues encountered. Exponents of these different views saw the need to test their conclusions in many contexts and compare them with other viewpoints. As a result, debates were held frequently on disputed issues, especially in the fields of Theology and Fiqh. These debates allowed both the systematic research steps to be followed to reach the truthto be revealed and opinions on disputed issues to be criticized and tested by the advocates of other views. Jadal works, which deal with the methods required to reveal the truth in debates also came to be seen as important by fiqh scholars and from the hijrī fourth century onwards, they began to compile works in this field. The obvious feature of these works is that they provide information on the manners and methods for carrying out debates and systematic research on controversial fiqh issues through legal examples while explaining some terms such as fard and binā'. In this article, the methods for asking and answering questions, which constitute one of the basic elements of the works of jadal written by fiqh scholars, will be examined through various prominent works, and the relevant terms will be explained. This study aims to reveal some of the basic principles that should be followed in systematic research and in debates among scholars using the question and answer method adopted by the fiqh scholars who compiled most jadal works.